2003
DOI: 10.1152/japplphysiol.00968.2002
|View full text |Cite
|
Sign up to set email alerts
|

Increased susceptibility to Pseudomonas aeruginosa infection under hindlimb-unloading conditions

Abstract: It has been reported that spaceflight conditions alter the immune system and resistance to infection [Belay T, Aviles H, Vance M, Fountain K, and Sonnenfeld G. J Allergy Clin Immunol 170: 262-268, 2002; Hankins WR and Ziegelschmid JF. In: Biomedical Results of Apollo. Washington, DC: NASA, 1975, p. 43-81. (NASA Spec. Rep. SP-368)]. Ground-based models, including the hindlimb-unloading model, have become important tools for increasing understanding of how spaceflight conditions can influence physiology. The obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
53
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 24 publications
3
53
1
Order By: Relevance
“…Our laboratory has shown, in previous studies, that hindlimb unloading of mice decreases resistance to infection (4,8,17) and that the use of countermeasures reduces these effects in this model (5). Hindlimb-unloaded mice were far more susceptible than control mice to infection with Klebsiella pneumoniae (8) and Pseudomonas aeruginosa (4).…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Our laboratory has shown, in previous studies, that hindlimb unloading of mice decreases resistance to infection (4,8,17) and that the use of countermeasures reduces these effects in this model (5). Hindlimb-unloaded mice were far more susceptible than control mice to infection with Klebsiella pneumoniae (8) and Pseudomonas aeruginosa (4).…”
mentioning
confidence: 91%
“…The acetylated forms of the last group are oligosaccharides with low molecular mass (5 kDa) and are believed to be the molecules responsible for the biological activities of AHCC (27,28,51). AHCC has been shown to have an enhancing effect on the immune system of humans (27) and rodents (10,28,47), including an increase of natural killer cell activity (25) and IL-12 production (49, 50).Our laboratory has shown, in previous studies, that hindlimb unloading of mice decreases resistance to infection (4,8,17) and that the use of countermeasures reduces these effects in this model (5). Hindlimb-unloaded mice were far more susceptible than control mice to infection with Klebsiella pneumoniae (8) and Pseudomonas aeruginosa (4).…”
mentioning
confidence: 99%
“…Spaceflight has been shown to alter the response of monocytes, isolated from astronauts preflight and in flight, to . Further, simulation of aspects of this microgravity-associated decreased immune response, using the hind limb unloaded mouse model, showed an enhanced susceptibility of these animals to bacterial infection (3,6). From the pathogen's perspective, bacterial obligate and opportunistic pathogens have been found to exhibit enhanced stress resistance phenotypes following growth under both true spaceflight and microgravity analogue conditions (13,30,33,(46)(47)(48)(49).…”
mentioning
confidence: 99%
“…High circulatory levels of these hormones are detected in individuals exposed to a variety of physically and/or mentally stressful situations, including trauma, space flight, and sepsis (13,29,31,32). The increases not only may alter the immune function but also may contribute to host morbidity and increased risk of infection (1,7,34). In the current study we reexamined the in vitro growth responses of a variety of bacterial species that were previously tested and reported not to be enhanced by the addition of NE (6,8).…”
mentioning
confidence: 99%
“…Although a great deal of evidence suggests that stress-induced neurohormones play a critical role in the outcome of infections (1,3,4,5,7,21,31), the mechanisms by which these hormones act in the host remain unclear. Studies with human and animal models have indicated that increased levels of stress hormones, including norepinephrine (NE), as well as other catecholamines, alter the immune response and physiology of the host (2).…”
mentioning
confidence: 99%